TINJAUAN ARTIKEL: MACAM-MACAM METODE PENGUJIAN AKTIVITAS ANTIOKSIDAN - Silvi Nugraheni, Tarisa; Setiawan, Iwan; Ardila Putri, Annisa; Wahyu Sukmawati, Aprillia; Nur Khasanah, Latifah; Khoirun Nisa, Logaritma; Nufus Hanyokro Putri, Lu'luin; Kisma Wulandari, Sindy; Amelia Riswana, Syifa (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2024)
Antioxidants are substances that fight and prevent the production of free radicals that can damage the body. The chemical structure, free radical sources, and physicochemical properties of preparations obtained from different samples can lead to different test results of antioxidant activity. Therefore, selective methods for analyzing antioxidant activity are needed for certain types of samples. Test methods for antioxidant activity include CUPRAC, DPPH, FRAP, HPLC, ORACFL, CAA, amperometric, voltammetric, and ABTS methods. The result from review are Antioxidant testing using the DPPH method is the most widely used method for measuring antioxidant activity as it is a quick, easy, and inexpensive assay. The DPPH method is based on the principle that a hydrogen atom of the DPPH radical is donated by an antioxidant compound, ultimately transferring DPPH to its reduced, non- radical form. Antioxidant testing uses his DPPH method in the field of cosmetic analysis to prevent free radicals that form in layers of the skin. Subsequently, in plant antioxidant tests, especially free radical measurements, the DPPH method is used to determine whether plant extracts have antioxidant activity.